Transformational Leadership in SMEs: Leveraging Initiative Climate and Employee Engagement for Enhanced Proactive Service Performance - Pratama , Chandra Bagus Agung; Soetjipto, Budi Eko; Wardoyo, Cipto; ., Sudarmiatin; Hardi , Richki; Pribadi , Agung Sakti; Ariyani, Linda Fauziyah (Journal of Ecohumanism, 2024)
This research explores the mediating role of initiative climate and employee engagement in the influence of transformational leadership on proactive service performance in Small and Medium Enterprises (SMEs) in Balikpapan. Adopting a quantitative approach and utilizing Structural Equation Modeling (SEM), the study surveys 200 employees from the service sector. The results reveal that transformational leadership significantly enhances proactive service performance. Additionally, it is found that the initiative climate and employee engagement mediate the relationship between transformational leadership and proactive service performance. The initiative climate is vital in fostering an environment that encourages proactive behaviors, while employee engagement boosts motivation and involvement in service tasks. These findings underscore the importance of transformational leadership in promoting superior service performance by creating an initiative-driven work climate and fostering high employee engagement. The practical implications suggest that SMEs should strengthen transformational leadership and cultivate an initiative climate alongside employee engagement to improve service performance.